PENENTUAN JUMLAH TENAGA KERJA YANG OPTIMAL PADA DEPARTEMEN TATA KELOLA & KEPATUHAN DENGAN METODE WORK SAMPLING DI PT PUPUK ISKANDAR MUDA - Rita Hartati; Putri Zuriati (Universitas Teuku Umar, 2018)
In this study, work observations were carried out using the Work Sampling method. Work Sampling method is used to see employee productivity in completing work. This research is also supported by the spread of the Nordic Standard Quaire Questionnaire (SNQ) to find out complaints experienced by workers. From the results of data processing, it is obtained that the standard time of each Worker / employee in completing their work is, Worker 1 is 60.13 minutes, Worker 2 is 59.236 minutes, Worker 3 is 59.035 minutes, Worker 4 is 60.218 minutes. The average percentage of workers working (productive) is 88.27% and the average percentage of workers doing idle is 11.73%. And from observing the work sampling method, there were 8 workers in the governance & compliance department.